Crisis as seen by the individual: the Norm Deviation Approach - Gaspar, R.; Barnett, J.; Seibt, B. (PsyEcology, 2015)
This paper presents a conceptual proposal applied to social, environmental and health crisis appraisal and coping: the Norm Deviation Approach. It is focused on the individual level and its interaction with the context within which a threat (or threats) has emerged. Thus far our understanding of the psychosocial processes that occur at the individual level during crises is a clear lacuna in the risk and crisis perception literature. As a first step for this understanding, we present a definition of crisis as perceived by the individual, based on three necessary components: (1) norm deviation; (2) appraisal; (3) coping. Despite the individual focus, the model is also cognizant of the social level, considering the system in which transactions between individuals and their social environment occur. This approach may be an initial step for developing experimental and computer modelling of societal crises, with practical implications for crisis prevention and monitoring, through social media analysis and other methods. Evidence from research focusing on specific aspects of the model and implications for crisis management and communication are also presented.